Drug Resistance Testing in HIV Infected Individuals on Treatment and Naive: Implications on Treatment Outcome - Winfrida Cheriro; Gideon Kikuvi; Simeon Mining; Wilfred Emonyi; Erick Rutto; Elijah Songok; Michael Kiptoo (Journal of HIV for Clinical and Scientific Research - Peertechz Publications, 2015)
Background: The Government of Kenya started offering ART in the public sector since 2003. Despite the dramatic reduction in AIDS related morbidity and mortality, the emergence and spread of drug resistance (DR) threatens to negatively impact on treatment regimens and compromise efforts to control the epidemic. Therefore, there is a need for information on the situation of DR Mutations (DRMS) and their implications on treatment. Objectives: To evaluate DRMS and their implications on treatment in HIV infected individuals attending Moi Teaching and Referral Hospital (MTRH) clinics. Method: In 2009, we consecutively collected plasma samples from two groups of HIV infected individuals, antiretroviral (ARV) naive and ARV experienced for more than 12 months and failing therapy according to world health organisation (WHO) guidelines. We performed genotypic DR using well established in-house Sanger sequencing methods. We then followed up the patients and compared the DRMS in relation to their drug regimens at the time of sample collection and16 months later. Results: We successfully extracted and sequenced 75 samples. Median age was 36.7 years.Out of 41 drug naive individuals only 3 had DRMS. Out of the 34 ARV experienced, 29 had DRMS to nucleoside reverse transcriptase inhibitor (NRTI), and 31 to non NRTI (NNRTI). After 16 months from sample collection date, 20/31(64%) ARV experienced patients with DRMS had not been changed therapy and only 5/20(25%) were susceptible to primary ARV while 12/14 changed were susceptible to new ARV. Conclusion: The information obtained in our study can serve as an indicator of ARV program efficiency in patients still on treatment, those who are to start treatment and those who are to be changed therapy due to failure. DR testing would be necessary before initiating and /or changing ART in order to achieve optimal clinical outcome.